STRATEGI DOSEN DALAM PEMANFAATAN HANDPHONE SAAT PERKULIAHAN PADA MAHASISWA JURUSAN PENDIDIKAN AGAMA ISLAM DI UIN ALAUDDIN MAKASSAR - Wahdaniah; Muhammad Rusmin B; Muhammad Yusuf Hidayat (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to: (1) describe lecturers’ strategies in directing the positive use of mobile phones during lectures, (2) identify forms of mobile phone utilization that support the learning process, (3) examine the obstacles in using mobile phones during lectures, and (4) describe solutions to overcome these obstacles. This research employed a qualitative approach conducted at the Department of Islamic Education, UIN Alauddin Makassar. The data sources consisted of lecturers and students of the 2023 cohort. Data were collected through observation, interviews, and documentation using observation and interview guidelines as research instruments. Data analysis followed the Miles and Huberman model, including data reduction, data display, and conclusion drawing and verification. Data validity was ensured through triangulation. The results show that: (1) lecturers’ strategies in directing the positive use of mobile phones are implemented by providing clear usage limitations during lectures, making their use more directed and educational rather than totally prohibited; (2) forms of mobile phone utilization include searching for additional references, conducting online attendance through Lentera, opening presentation or paper files, and participating in online quizzes; (3) the main obstacles include limited Wi-Fi and internet access, insufficient phone storage capacity, and limited battery life; and (4) solutions include sharing hotspots, borrowing devices, downloading materials in advance, using cloud storage, and saving battery usage. The findings imply that lecturers in the Department of Islamic Education at UIN Alauddin Makassar are expected to continuously develop effective strategies in directing the positive use of mobile phones so that technology can function as a learning support tool rather than a distraction.